2005
DOI: 10.1074/jbc.m413522200
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Secretion by Gastric Epithelial Cells Is Regulated by E Prostaglandins and MAPKs

Abstract: Because matrix metalloproteinases (MMPs) play roles in inflammatory tissue injury, we asked whether MMP secretion by gastric epithelial cells may contribute to gastric injury in response to signals involved in Helicobacter pylori-induced inflammation and/or cyclooxygenase inhibition. Tumor necrosis factor (TNF)-␣, interleukin (IL)-1␤, and epidermal growth factor (EGF) stimulated gastric cell MMP-1 secretion, indicating that MMP-1 secretion occurs in inflammatory as well as noninflammatory situations. MMP-1 sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
0
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 73 publications
3
62
0
2
Order By: Relevance
“…Matrix metalloproteinases (MMPs) are neutral proteases that act extracellularly to digest collagen and other connective tissue molecules. MMP dysregulation plays a critical role in tissue destruction in rheumatoid arthritis (RA) (86,87) and in gastric ulceration (88) and atherogenic vascular damage (89,90). Statins have been reported to decrease production of MMPs 1, 3, and 9 in human macrophages and vascular smooth muscle cells (91), MMPs 1 and 9 in carotid plaques (85), and MMP-3 in IL-1␤-stimulated chondrocytes (92).…”
Section: Statins As Antiinflammatory Drugs: Effects On Cells and Tissuesmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are neutral proteases that act extracellularly to digest collagen and other connective tissue molecules. MMP dysregulation plays a critical role in tissue destruction in rheumatoid arthritis (RA) (86,87) and in gastric ulceration (88) and atherogenic vascular damage (89,90). Statins have been reported to decrease production of MMPs 1, 3, and 9 in human macrophages and vascular smooth muscle cells (91), MMPs 1 and 9 in carotid plaques (85), and MMP-3 in IL-1␤-stimulated chondrocytes (92).…”
Section: Statins As Antiinflammatory Drugs: Effects On Cells and Tissuesmentioning
confidence: 99%
“…The cultures were incubated for the indicated times at 37°C, and supernatants collected, concentrated, and analyzed, as described (23). Adherent cells were washed 3 times with cold phosphate-buffered saline, lysed (20 mM Tris, pH 7.4, 1 mM EGTA, 2 mM sodium vanadate, 25 mM sodium fluoride, 0.5% (v/v) Triton X-100, 2 mM phenylmethylsulfonyl fluoride, 10 5 kallikrein units/ml aprotinin, and 10 g/ml each of chymostatin, antipain, and pepstatin) for 20 min at 4°C, as described (36), and lysates collected and used directly or frozen for further study.…”
Section: Methodsmentioning
confidence: 99%
“…In response to H. pylori and gastrin, secretion of MMP-7 and MMP-9, respectively, may be regulated by ERK (26,43). In response to cytokines, ERK mediates, and p38 inhibits, gastric cell MMP-1 secretion (23). Because the primary connective tissue components of gastric stroma are proteins susceptible to MMP-1 degradation (29,44,45), MMP-1 secretion may be particularly relevant to the pathogenesis of gastric damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating data has revealed that COX-2 expression is not limited to sites of inflammation (Ek et al, 2001). COX-2 and COX-2 derived prostanoids have been implicated in the biological processes of angiogenesis (Ben-Av et al, 1995), proliferation (Gately and Li, 2004), apoptosis (Gilroy et al, 2003), cell adhesion (Pillinger et al, 2005) and inflammatory resolution (Gilroy et al, 1999;Wallace and Devchand, 2005) through COX-2-dependent and independent mechanisms (Tegeder et al, 2001). Cancer prevention by tNSAIDs and coxibs is partially due to their modulation of alternative eicosanoid pathways, which are non-COX-2 effects (Rigas and Kashfi, 2005) not requiring the presence of COX-2 enzyme.…”
Section: Introductionmentioning
confidence: 99%